Histopathological Changes in Brain Tissuesassociated Withoral Administration of Tramadol in Male Rats (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Repeated and long treatment with tramadol might lead to accumulation of toxic metabolites inthe body and increase the risk for pharmacokinetic interaction and decrease the clearance of tramadol,thereforethis studywas performed to investigate the toxic impact of the tramadol on the tissues of the brain in themale rats.Method: The experiment was carried out at Environmental Toxicology Laboratory, Department of EnvironmentalStudies, Institute of Graduate Studies and Research, Alexandria University, Alexandria, Egypt.Thirty-two AlbanoWaster male rats weighing (200-250 g) were obtained from the animal house of the Faculty of Medicine,Alexandria University, andgrouping into four groups (8 rats for each group in each cage). The Control groupwas fed a basal diet and given tap water daily for ten days. In group two the rats were fed basal diet andgiven Tramadol HCL orally in dose 45mg/ kg .B.W dissolved in (5ml) normal saline (0.9%) by gastric tube,daily for Ten days. In group three the rats were fed with basal diet and given Tramadol HCL orally in dose45mg/ kg .B.W dissolved in (5ml) normal saline (0.9%) by gastric tube, daily for Twenty days. The groupfor the rats was fed with basal diet and given Tramadol HCL orally in dose 45mg/ kg .B.W dissolved in(5ml) normal saline (0.9%) by gastric tube, daily for Thirty days. At the end of the experimental period Kidneytissues of each rat were immediately removed and after weighted put into 10% neutral buffer formalin as afixative solution and stained with Hematoxylin –Eosin stain.The Results: The results observed a significant decrease in the weight of the brain in the groups of therats that were given the Tramadol HCL in dose 45mg/ kg .B.W with increasing the time of administrationas compared with the control group. Histopathological changes were observed in rats brain tissues sectionthe rats that given Tramadol HCL orally in dose 45mg/ kg .B.W dissolved in (5ml) normal saline for tendays revealed a mild degree of tissue injury in the cerebral cortex, with few vacuolar degeneration anddilatation of blood vessels, and the tissue sections of grouptwoafter ten days revealed a mild degree of tissueinjury in the cerebral cortex, with few vacuolar degeneration and dilatation of blood vessels, whilethe threegroupsObserved increase in the vacuolar degeneration, with neural atrophy and degeneration of neuronswith reduction the neural process and pyknosis of the nuclei dilatation of blood vessels after twenty days oftramadol administration. The tissue Sections obtained from group four after thirty days revealed an increasein the vacuolar degeneration, with more atrophy of the neural cells and complete reduction of the neuralprocess and pyknosis of the nucleus in the injured neural cells and gliosis.The conclusion of this study there are harmful toxic effects when administrated tramadol for long period onthe brain tissues, therefore an abuse of tramadol should be avoided except with medical prescription owingto its toxic effects.